2008
DOI: 10.1634/stemcells.2008-0432
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Patterned Stem Cell Differentiation Within Multicellular Structures

Abstract: The ability of stem cells to differentiate into specified lineages in the appropriate locations is vital to morphogenesis and adult tissue regeneration. Although soluble signals are important regulators of patterned differentiation, here we show that gradients of mechanical forces can also drive patterning of lineages. In the presence of soluble factors permitting osteogenic and adipogenic differentiation, human mesenchymal stem cells at the edge of multicellular islands differentiate into the osteogenic linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
359
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(382 citation statements)
references
References 34 publications
17
359
5
1
Order By: Relevance
“…4d). These results confirm previous studies, in which the ability of a cell to generate tension and spread on two-dimensional substrates leads to osteogenic differentiation, whereas rounded cells primarily undergo adipogenic differentiation [40][41][42][43] . However, there has been no previous work to investigate hMSC differentiation responses to changing substrate stiffness.…”
Section: Resultssupporting
confidence: 91%
“…4d). These results confirm previous studies, in which the ability of a cell to generate tension and spread on two-dimensional substrates leads to osteogenic differentiation, whereas rounded cells primarily undergo adipogenic differentiation [40][41][42][43] . However, there has been no previous work to investigate hMSC differentiation responses to changing substrate stiffness.…”
Section: Resultssupporting
confidence: 91%
“…Numerous studies have shown that the mechanical properties of the cell's microenvironment, such as the substrate stiffness, have a fundamental effect on hMSC cell fate and function and impact tissue regeneration 6, 7, 8, 9. Recently, evidence is rising that the geometrical properties of the cell's environment also play an important role as regulators of cell behavior 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. Using geometric features, such as pore geometry, as a cue to direct tissue regeneration is compelling since it may allow a biomaterial to steer cell function purely by its shape and hereby contribute to tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies related to the effect of nanotopography on cellular behavior indicated that osteoblast adhesion and functionality was enhanced by 30% when cultured on a nanograined Al 2 O 3 and TiO 2 substrate (4-6) compared with those cultured on a micrograined surface, and nanostructures such as TiO 2 nanotubes with Ͻ100-nm spacing showed superior characteristics in bone mineral synthesis (5). However, most of the previous studies on nanostructures and cell responses have mainly used oriented, patterned, or semiordered polymer arrays (7)(8)(9) and alumina/ polymer hybrid patterned arrays (10).…”
mentioning
confidence: 99%